Moro Muslims In Southern Phillippines: The Rise of Abu Sayyaf and the Genealogy of Conflict In Southeast Asia - Herdi Sahrasad; Adhe Nuansa Wibisono; Al Chaidar Al Chaidar (Ulumuna, 2018)
The main problem of Moro Muslims in Southern Philippines are now the right to self-determination but it also include poverty, underdevelopment, low education, unemployment, discrimination, and violent conflict. Upon the Spanish colonization for more than three centuries (1521-1898), the Moros were controlled by the United States for almost five decades (1898-1942). Japan colonised them for three years before they were integrated to the Republic of Philippines in 1946. Their struggle for independence still continues today represented by the Moro National Liberation Front (MNLF), establihsed in the late 1960s and led by Nur Misuari, and by the Moro Islamic Liberation Front (MILF) led by Salamat Hasyim in 1981. The birth of the MILF was a response to dissatisfaction with the MNLF that was considered less assertive in fighting for Bangsamoro's rights and too accommodative to the Philippine government. In early 1990s, Abu Sayyaf Group (ASG) led by Abdulrajak Janjalani emerged to respond the situation. In later development, it rises to become a prominent group involved in a long-standing conflict and terror in this landmark of Southeast Asia region.